Fitness and anthropometric profiles of international vs. national judo medalists in half-heavyweight category - Drid, P.; Casals, C.; Mekic, A.; Radjo, I.; Stojanovic, M.; Ostojic, S. M. (The Journal of Strength and Conditioning Research, 2015)
The aim of the study was to determine the anthropometric and fitness profiles of European half-heavyweight judokas by success in competition. For this purpose, we compared 5 international medalists (elite) with 5 national medalists (subelite). All male judokas won at least 1 medal in the half-heavyweight category during the previous 2 years. The testing in this cross-sectional study was performed during 4 days. All subjects underwent anthropometric assessment with body mass, height, skinfold, and limb circumference measures, and the body fat percentage was estimated by manual bioimpedance. The physical fitness evaluation consisted in peak torques for thigh and shoulder muscles, handgrip strength, high and long jumps, medicine ball throw, pull-ups, deadlift, bench press, deep squat, VO2max, Max Power, and Tokui Waza tests. The statistical analysis by the Student's t test showed significant differences for forearm and upper-arm circumferences, peak torques, pull-ups, bench press, deadlift, deep squat, VO2max, Max Power, and Tokui Waza tests. Our results showed that elite judokas have a superior fitness profile than subelite athletes from the half-heavyweight category. Moreover, elite judokas seem to have a higher arm muscle mass than subelite athletes but a similar body fat percentage. This study could be of interest for judo coaches with athletes competing in the half-heavyweight category, as some tests that discriminate by judo success for this specific weight category are described. Few studies analyze anthropometric and fitness profiles in half-heavyweight male judokas, so additionally our results can be used as a reference for coaches, athletes, and scientists.